Analisis Kinerja Keuangan dan Penilaian Saham PT Aneka Tambang Tbk sebagai Dasar Keputusan Investasi - Iswardhani, Indri; Bando, Ushwa Dwi Masrurah Arifin; Sarah, Nulthazam; Sandira, Nur Fadilah Ayu; Nasir, Sri Astuti (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2025)
This study aims to analyze the financial performance and assess the fairness of the stock price of PT Aneka Tambang Tbk (ANTM) as a basis for investment decision-making. The approach used is fundamental analysis, measuring five key financial ratios: Return on Equity (ROE), Dividend Payout Ratio (DPR), Earnings per Share (EPS), Dividend per Share (DPS), and Price to Earnings Ratio (PER). In addition, the intrinsic value of the stock is estimated using the PER method and compared to the market price (closing price) to determine its valuation status—whether undervalued, fairly valued, or overvalued. The findings show that during the 2020–2024 period, ANTM recorded stable growth in EPS and DPS, along with a significantly increasing DPR policy. However, the intrinsic value of the stock in Q2 2025 is estimated at Rp1,526.24, which is considerably lower than the market price of Rp3,040, categorizing the stock as overvalued. Based on this analysis, the recommended investment decision is to re-evaluate the feasibility of purchasing ANTM shares. This study emphasizes the importance of using fundamental analysis to understand the balance between a company's financial performance and market expectations in investment decision-making.